Storyscaping : stop creating ads, start creating worlds - Legorburu, Gaston; McColl, Darren (Hoboken, N. J. : John Wiley & Sons, 2014)
How to use powerful tools to engage customers with your brand Marketers, technologists, and corporate leaders are looking for ways to more effectively connect consumers with their brand. Storyscapes introduces''storyscaping'' as a way to create immersive experiences that solve the challenge of connecting brands and consumers. This book describes a powerful new approach to advertising and marketing for the digital age that involves using stories to design emotional and transactional experiences for customers, both online and offline. Each connection inspires engagement with another, so the bra.
Keywords: Advertising; Storytelling; Branding (Marketing)